Comments on energy harvesting on a 2:1 internal resonance portal frame support structure, using a nonlinear-energy sink as a passive controller - Rocha, Rodrigo T. [UNESP]; Balthazar, Jose M. [UNESP]; Tusset, Angelo M.; Piccirillo, Vinicius; Felix, Jorge L. P. (Praise Worthy Prize, 2016)
This paper presents an application of a passive control strategy in a base-excited two-degrees-of-freedom portal frame support structure considering extract energy using a piezoelectric material coupled to a column. The 2:1 (two-to-one) internal resonance is set between the vertical and horizontal coordinates, resulting in a phenomenon known as saturation. This phenomenon transfers partial vibratory mechanical energy from vertical to horizontal mode, making possible to extract energy from the columns. The idea is to tune the vibration of the structure, in order to improve the energy harvesting, and this is performed through a passive controller that is a nonlinear-energy sink device, i.e., the proposed device is a mass-springdamper that plays a role of tuning the vertical and horizontal displacements, and, as consequence, improving the energy harvesting. The numerical results depicted the best configuration of the controller device, which aims to improve the energy harvesting, whose piezoelectric material is used as a means of low-power energy transduction.
Keywords: Energy harvesting; Nonlinear-energy sink; Passive control; Saturation phenomenon